(untitled) (Advancements in Homeopathic Research, 2024)
Introduction: Technological advancement in homeopathic quality control helps for more accuracy in data & consumes less time. Technology progression has led to inclusion of modern instruments like UV spectroscopy, HPTLC, gas chromatography in homeopathic quality control. Assessment of alcohol percentage in homeopathic mother tincture is an essential quality parameter. However, estimation of alcohol percentage by using conventional method (CM) as described in Homeopathic Pharmacopoeia of India is time consuming at commercial level. Advanced technology of gas chromatography with head space (GCHS) is considered to minimise the process time, improve the efficiency, and provide more accuracy. However, there is no study to validate this statement in homeopathic industry. This study is aimed to find out the difference in both the methods.